2023
DOI: 10.5334/aogh.3994
|View full text |Cite
|
Sign up to set email alerts
|

Potential New Approaches for Prostate Cancer Management in Resource-Limited Countries in Africa

Abstract: Prostate cancer is a major male malignancy in many sub-Saharan countries in Africa. Because of resource limitations, screening, early detection, diagnosis, and curative treatments are not available for many men on the subcontinent, and there are even barriers to the treatment of advanced-stage metastatic prostate cancer. We are making the case for new approaches to the detection, diagnosis, and treatment of this malignancy in sub-Saharan Africa and other low-resource regions-approaches that differ from the one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In contrast, some developing countries or poor regions may face the challenges of limited funding and inadequate research conditions, resulting in a relative lag in scientific research. In this way, a contradiction has arisen between developing countries with limited medical technology but high PC morbidity and mortality and developed countries with advanced medical technology but reduced PC morbidity and mortality[ 25 , 26 ]. Therefore, developed countries should proactively conduct international exchanges and cooperation in the field of PCLM to promote the sharing of data, funds and equipment, technology and methods, and the establishment of international cooperation networks.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some developing countries or poor regions may face the challenges of limited funding and inadequate research conditions, resulting in a relative lag in scientific research. In this way, a contradiction has arisen between developing countries with limited medical technology but high PC morbidity and mortality and developed countries with advanced medical technology but reduced PC morbidity and mortality[ 25 , 26 ]. Therefore, developed countries should proactively conduct international exchanges and cooperation in the field of PCLM to promote the sharing of data, funds and equipment, technology and methods, and the establishment of international cooperation networks.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant in geographic areas where the highest prostate cancer mortality rates are found, such as the Caribbean, sub-Saharan Africa, and parts of the former Soviet Union [ 62 ]. Unfortunately, very few clinical trials have been carried out in low- and lower-middle-income countries [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another approach that has been explored is to use alternative screening tools that are more accessible and affordable in SSA. A review published by Bosland et al [14] suggested that there is a need for cost-effective options to measure serum PSA levels that do not rely on laboratory quality control constraints. A quick and simple test for PSA has been developed using techniques similar to those used for rapid COVID-19 antigen tests.…”
Section: Screeningmentioning
confidence: 99%